The Influence of Culturally Responsive Teaching Learning Model with Number Wheel Media on Mathematics Learning Outcomes at Pandan Malaysia Learning Center - Dianis, Iffada Hayu; Nasution, Dewi Kesuma (Journal of English Language and Education, 2025)
This study was initiated due to challenges in student learning activities, particularly in mathematics. The teaching method used was predominantly lecture-based and teacher-centered, which led to student boredom and low learning outcomes. Educators mostly employed lectures and question-and-answer sessions without incorporating varied strategies or engaging media. As a result, students showed limited improvement in mathematics performance. The research aimed to examine the impact of the Culturally Responsive Teaching (CRT) model, supported by the use of number wheel media, on the mathematics learning outcomes of grade II students at the Pandan Malaysia Learning Studio. This study used a quantitative research approach with a one-group experimental design. The sample included all 13 grade II students at the studio. The research instrument was a mathematics test consisting of 12 validated items, administered as both a pre-test and a post-test. Findings showed a significant improvement in student outcomes after implementing the CRT model with number wheel media. The average score of the control class was 58.00, while the experimental group that used the innovative method scored an average of 79.23. Based on the “Independent Samples Test,” the significance value (sig. 2-tailed) was 0.000, which is less than 0.05, indicating a statistically significant effect. In conclusion, the study found that the Culturally Responsive Teaching model, when combined with number wheel media, positively influenced the mathematics learning outcomes of grade II students at the Pandan Malaysia Learning Studio, highlighting the importance of engaging, student-centered learning strategies.